1997
DOI: 10.1002/pro.5560060510
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, expression, and characterization of the genes for mouse FcγRIIb1 and FcγRIIb2 cytoplasmic regions

Abstract: The cytoplasmic regions of the mouse low-affhity FcyRII isoforms, mFcyRIIb1, and mFcyRIIb2, play a key role in signal transduction by mediating different cellular functions. mFcyRIIbl has a 94-residue cytoplasmic region, whereas mFcyRIIb2 has a 47-residue cytoplasmic region. Genes encoding the cytoplasmic regions of mFcyRIIbl (bl-94) and mFcyRIIb2 (b2-47) were designed, synthesized, and expressed as fusion proteins in Escherichia coli. A sequencespecific protease, thrombin, was used to release the bl-94 peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Therefore, the cytoplasmic region of mFcγRIIb1 almost certainly interacts directly with the phospholipid surface. Previous work has demonstrated that the b1-94 peptide, a rather large ≈10 kDa peptide, is largely unstructured in aqueous solutions but that nonaqueous solvents such as trifluoroethanol and methanol induce significant structure (26). Therefore, the result that b1-94 binds to phospholipid membranes suggests that this nearby surface may be crucial to the in vivo structure of the cytoplasmic region of mFcγRIIb1.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the cytoplasmic region of mFcγRIIb1 almost certainly interacts directly with the phospholipid surface. Previous work has demonstrated that the b1-94 peptide, a rather large ≈10 kDa peptide, is largely unstructured in aqueous solutions but that nonaqueous solvents such as trifluoroethanol and methanol induce significant structure (26). Therefore, the result that b1-94 binds to phospholipid membranes suggests that this nearby surface may be crucial to the in vivo structure of the cytoplasmic region of mFcγRIIb1.…”
Section: Discussionmentioning
confidence: 99%
“…Because these peptides are covalently attached to the plasma membrane in vivo, the results strongly suggest that the cytoplasmic region of mFcγRIIb1 is in the membranebound state in intact cells. Because this peptide has very little structure in aqueous solution (26), it is possible that the membrane surface confers structure on this peptide. The association of the b1-94 peptide with phospholipid vesicles is weakly dependent on the phospholipid composition and Ca 2+ concentration, raising the possibility that membrane binding by the mFcγRIIb1 cytoplasmic region might be modulated by these factors in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations